Mothers’ experiences of maternity services: internal consistency and test–retest reliability of the Greek translation of the Kuopio Instrument for Mothers - Sapountzi-Krepia, Despina; Tzavelas, George; Psychogiou, Maria; Clark, Lynn; Vehvilainen-Julkunen, Katri; Raftopoulos, Vasilios (My University, 2007)
Objective: the Kuopio Instrument for Mothers (KIM) questionnaire assesses mothers’ experiences of maternity services during pregnancy and delivery. The aim of this study was to translate the questionnaire into Greek, and to evaluate the internal consistency and test–retest reliability of the Greek version of the KIM. Methods: 77 mothers completed both the test and the retest questionnaire. The KIM includes the Utah Test for the Childbearing Year (UTCY) and four other scales. Internal consistency was assessed using Cronbach’s alpha. Test–retest reliability was assessed using intraclass correlation coefficients, kappa coefficients (k) and Pearson correlation coefficients (r). Findings: strong correlation (r ¼ 0.793, po0.001) was found between the total test mean score (88.2275.82) and the total retest mean score (87.4976.16) for the UTCY. Cronbach’s alpha ranged from 0.74 for the UTCY to 0.75 for the 26-item scale on discussion of topics in maternity welfare clinics, 0.85 for the 10-item scale on mother–obstetrician collaboration, 0.94 for the 14-item scale on mother–midwife collaboration, and 0.55 for the seven-item scale on provision of services for women. The k coefficients ranged from 0.325 to 0.924. Conclusions: the questionnaire appears to be a reliable measure of mothers’ experiences in the Greek population. Further studies are needed to refine the instrument.
Keywords: Greek mothers; Maternity services; Delivery; Kuopio Instrument for Mothers; Test–retest reliability